100 hugs - Riddell, Chris 1962- (Macmillan Children's Books, an imprint of Pan Macmillan, 2017)
This gorgeous collection of hugs from Children's Laureate Chris Riddell is the perfect gift for a loved one, or to cheer yourself up on a dark day. It covers every possible type of hug you can think of, but one thing is for certain: every one will touch your heart
"A book to warm the hearts of those in need of a hug"--Cover
Keywords: Umarmung; Hugging / Juvenile literature; Hugging; Picture books for children; Juvenile works; Picture books; Children's picture books; Bilderbuch